A new human breast cancer cell line, KPL-3C, secretes parathyroid hormone-related protein and produces tumours associated with microcalcifications in nude mice. - Kurebayashi, J. (Nature Publishing Group, 1996)
Parathyroid hormone-related protein (PTHrP) is the main cause of humoral hypercalcaemia of malignancy (HHM). We recently established a new human breast cancer cell line, designated KPL-3C, from the malignant effusion of a breast cancer patient with HHM. Morphological, cytogenetic and immunohistochemical analyses indicated that the cell line is derived from human breast cancer. The KPL-3C cells stably secrete immunoreactive PTHrP measured by a two-site immunoradiometric assay, possess both oestrogen and progesterone receptors and are tumorigenic in female nude mice. The addition of phorbol-12-myristate-13-acetate to the medium significantly increased PTHrP secretion from the cells. In contrast, hydrocortisone, medroxyprogesterone acetate and 22-oxacalcitriol decreased PTHrP secretion in a dose-dependent manner. Unexpectedly, a number of microcalcifications were observed in the transplanted tumours. Radiographical examination indicated that the microcalcifications in the tumours are very similar to those commonly observed in human breast cancer. These findings suggest that this KPL-3C cell line may be useful for studying the regulatory mechanisms of PTHrP secretion and the mechanisms that lead to the deposition of microcalcifications in breast cancer. IMAGES: